Perilaku Agresi Verbal dan Perilaku Agresi Relational pada Remaja Perempuan - Hapsah, Sitti; Muslim, Azis (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2021)
he purpose of this study was to determine the phenomenon of aggressive behavior in adolescent girls in grade 10 Ips Madrasah Aliyah Swasta Darul Dakwah wal Irsyad Palu City which is a religious-based school but has a serious case record. This research includes fieldresearch with a descriptive qualitative approach. The data sources in this study were 1 BK teacher, and 5 female students in class 10 Social Studies. Data collection methods used are interviews, observation and documentation. The analysis technique uses interactive analysis. The results of this study indicate that aggressive behavior is the source of juvenile delinquency cases, namely verbal and relational aggression, this aggressive behavior occurs in female students and verbal and relational aggression behavior is easy to develop in the school because some of the female students come from a family background that is not harmonious and comes from from an unhealthy environment and negative circle of friends.